Evaluating indoor air quality and energy impacts of ventilation in a net-zero energy house using a coupled model. (7th February 2018) - Ng, Lisa; Poppendieck, Dustin; Dols, W. Stuart; Emmerich, Steven J.
Abstract : The National Institute of Standards and Technology constructed the Net-Zero Energy Residential Test Facility to support the development and adoption of cost-effective net-zero energy designs and technologies. In support of indoor air quality goals, contaminant source control approaches were implemented that minimized the use of products containing urea-formaldehyde resin and utilized products with relatively low volatile organic compound emissions. Indoor and outdoor concentrations of formaldehyde and acetaldehyde were approximately measured monthly for 15 months. Independent emission measurements of formaldehyde were made in a small chamber system to determine the emission rates from samples of the wood flooring, plywood, and wood cabinetry taken from the house. Blower door tests were performed to determine the leakage area of the exterior envelope, the interior floors, and transfer grilles between floors. Real-time formaldehyde concentration and energy measurements were used to verify the indoor concentrations and energy predictions of a coupled CONTAM-EnergyPlus model of the house. The verified model was then used to evaluate the impacts of different outdoor air ventilation rates on indoor concentrations and energy. The current work demonstrates the need for consideration of source control options during product selection and the provision of mechanical ventilation, especially in homes with relatively airtight envelopes.